Interannual variability of precipitation in Sri Lanka: comparative study of observation periods 1881-1980, 1931-1980, 1951-1980 - NAUMANN, M. (MAUSAM, 1990)
On the basis of the annual absolute rainfall totals over a 100-year period (1881-1980) the interannual rainfall variability of 14 meteorological stations Sri Lanka is being discussed by means of different statistical indices in comparison with the observation periods 1931-1980 and 1951-1980. Number, frequency and probability of occurrence of drought (<75%) of the arithmetical rainfall mean), drought-free (>75%) and wet years (>125 %) were examined under temporal and regional aspect (wet and dry zone of Sri Lanka). There is a very distinct rainfall variability in all three observation periods with in the dry zone in the wet zone, the drought years within longer drought-free periods are fewer an occur sporadically. According to an evaluation key the drought years .1975-1978 are on an extraordinary high level comparable only with the years 1908-1911. Drought years with a maximum intensity are 1974 (with in the dry zone) and 1908(1976 (within the wet zone) and wet years 1957 {in dry Zone) and 1963 (in wet zone).